PRIMARY PRODUCTIVITY OF JAKARTA BAY IN A CHANGING ENVIRONMENT: CLIMATE CHANGE AND ANTHROPOGENIC IMPACTS - Vincentius Siregar; Alan F. Koropitan (BIOTROPIA, 2013)
Jakarta Bay receives direct impact from the rapid development of infrastructure and landbased industries which contributed to the increase in pollution and nutrient, and at the same time facing climate change. This condition influenced growth of chlorophyll- and primary production. To investigate changes of primary production in Jakarta Bay due to anthropogenic and climate change impacts, a field measurement, laboratory experiment and collection of several data sets have been conducted. The study showed that impact of anthropogenic, particularly sediment load from the land to primary production is important. The intensification of primary production occurs in the middle region of Jakarta Bay, while the chlorophyllconcentration is high in the river mouth area. The anthropogenic impact is indicated by the land use change that has increased to 73% during the last ten years. The laboratory experiments by injecting CO in the waters, as a global warming simulation, have shown a decrease in chlorophyll- and primary production. Therefore, the combination of anthropogenic and climate changemay have a double impact on the Jakarta Bay ecosystem.Key words: Primary production, Jakarta Bay, anthropogenic, climate change, impact